Comparison of short-term clinical outcomes between open-wedge high tibial osteotomy and tibial condylar valgus osteotomy - Takashi Higuchi; Hironobu Koseki; Akihiko Yonekura; Chieko Imai; Iku Tomonaga; Shinya Sunagawa; Umi Matsumura; Makoto Osaki (BMC Musculoskeletal Disorders, 2024)
Abstract Background This study aimed to compare radiological features and short-term clinical outcomes between open-wedge high tibial osteotomy (OWHTO) and tibial condylar valgus osteotomy (TCVO), to provide information facilitating decision-making regarding those two procedures. Methods Twenty-seven cases involving 30 knees that had undergone OWHTO (HTO group) and eighteen cases involving 19 knees that had undergone TCVO (TCVO group) for medial compartment knee osteoarthritis (OA) were retrospectively evaluated. Patient characteristics, severity of knee OA, lower limb alignment, joint congruity and instability were measured from standing full-length leg and knee radiographs obtained before and 1 year after surgery. Range of motion in the knee joint was measured and Knee Injury and Osteoarthritis Outcome Score (KOOS) was obtained to evaluate clinical results preoperatively and 1 year postoperatively. Results Mean age was significantly higher in the TCVO group than in the HTO group. Radiological features in the TCVO group included greater frequencies of advanced knee OA, varus lower limb malalignment, higher joint line convergence angle, and varus-valgus joint instability compared to the HTO group before surgery. However, alignment of the lower limb and joint instability improved to comparable levels after surgery in both groups. Maximum flexion angles were significantly lower in the TCVO group than in the HTO group both pre- and postoperatively. Mean values in all KOOS subscales recovered similarly after surgery in both groups, although postoperative scores on three subscales (Symptom, Pain, and ADL) were lower in the TCVO group (Symptom: HTO, 79.0; TCVO, 67.5; Pain: HTO, 80.5; TCVO, 71.1; ADL: HTO, 86.9; TCVO, 78.0). Conclusions Both osteotomy procedures improved short-term clinical outcomes postoperatively. TCVO appears preferable in cases of advanced knee OA with incongruity and high varus-valgus joint instability. An appropriate choice of osteotomy procedure is important to obtain favorable clinical outcomes.